Effectiveness of Comics to Train Students’ Critical Thinking Skills in Physics Learning: A Mini-Review - Saidatul Khoiriyah; Nadi Suprapto (Indonesia Approach Education, 2021)
Critical thinking skills, namely intelligence, is needed by students in the 21st century period. Interpretation, analysis, evaluation, conclusions, and explanations are some of the cognitive indicators of critical thinking. One way to practice impressive critical thinking skills is to use comics as media. Comics are one of the benefits of improving the learning process because they have several aspects that can attract students' learning interest to understand the material to be conveyed through visualizing images and stories in comics. The research was intended to explain comic media's effectiveness to train students' critical thinking skills in learning physics. The research used a literature search in journals that can be accounted for in comic media and critical thinking skills. Data analysis techniques in library research applied descriptive qualitative research. Physics comics that are digital-based can attract students' interest because they can be used anytime and anywhere to strengthen students' critical thinking skills. The learning outcomes of students can be more effective and contextual. The literature search results obtained indicate that comic media is useful in training students' critical thinking skills.